ACCESUL LA RESURSELE INFORMAŢIONALE ŞTIINŢIFICE ÎN BIBLIOTECILE DIN REPUBLICA MOLDOVA - ŢURCAN, Nelly (BIBLIOPOLIS, 2020)
The article presents the study results on the access to the scientific information ressources in the libraries of the Republic of Moldova. The majority of respondents are satisfied by the access to scientifical journals. In order to improve the access the researchers consider that the library should to change the policy of subscription to scientific journals and to organize various information activities, to implement innovative project of institution digital repository.